Hysterosalpingography (HSG) Examination Management in Infertility Clinics at Permata Cirebon Hospital - Maesaroh, Nur; Laksono, Muharram Budi; Priyono, Habib; Aviv Pasa, Muhammad; Qodri; Safitri, Eka (Universitas An Nasher - Cirebon, 2025)
Background: Hysterosalpingography (HSG) is a radiological examination used to evaluate the uterus and fallopian tubes by injecting contrast media, making the anatomical structures appear more opaque. This procedure is commonly performed in cases of clinical infertility. Purpose: This study aims to describe the implementation of HSG procedures at Permata Hospital Cirebon, including the technique of contrast media injection, the types of projections used, and the approaches taken to enhance patient comfort and minimize radiation exposure, considering the limitations of the available equipment. Methods: This study employed a qualitative descriptive method involving three samples, using observation checklists and interview sheets as research instruments. The examination was conducted on days 9 to 11 of the menstrual cycle using a catheter for contrast media insertion. The projections used were AP Supine and oblique as an additional projection. Post-evacuation imaging was not performed on the AP Supine projection as the obtained images were sufficient for diagnosis. The contrast media was inserted using a catheter instead of a salpingograph, which provided greater patient comfort. Due to equipment limitations, the HSG procedure at Permata Hospital Cirebon was performed using a conventional X-ray machine rather than fluoroscopy, thereby reducing the patient’s radiation exposure. Results: HSG examinations without post-evacuation imaging remained diagnostic, as the plain and post-contrast images were sufficient. The use of a catheter was preferred for its comfort, sterility, and availability. The procedure was conducted without fluoroscopy to reduce radiation exposure, although ideally, fluoroscopic guidance is recommended to allow real-time monitoring of contrast injection and to minimize image repetition.